Analytical calculations of the angles of rotational transform specified by different plasma pressure profiles and an external transverse magnetic field in the torsatron - Kuznetsov, Yu.К.; Pinos, I.B.; Tyupa, V.I. (Вопросы атомной науки и техники, 2003)
The authors of the present work have calculated the angles specified by various plasma pressure profiles depending on the parameter α that characterizes the profile of vacuum angles of rotation angles and on the magnetic axis displacement caused by an external transverse magnetic field. The authors have considered three laws of plasma pressure distribution over vacuum magnetic surfaces: P₁=P₀, P₂=P₀(1-y(r)/y(r₀)); Р₃=Р₀(1-y(r)/y(r₀))². The calculations showed, that in the case of magnetic axis shifting into the inside of the torus and at low values of α, the rotational transformation angle of a torsatron decreases up to zero with plasma pressure increasing. In this case, the splitting of magnetic surfaces caused by pressure distributions Р₃=Р₀(1-y(r)/y(r₀))² takes place in the central region of a magnetic configuration. As plasma pressure distributed by the law P₁=P₀ increase the splitting of magnetic surfaces due to the helical winding perturbation only occurs. Авторами роботи виконані розрахунки кутів обертального перетворення, зумовлених різними розподілами тиску плазми в залежності від параметра α, характеризую чого розподіл вакуумних кутів повороту силових ліній, а також від зміщення магнітної осі, викликаного зовнішнім поперечним магнітним полем. Авторами роботи розглянуто три закони розподілу тиску плазми по вакуумним магнітним поверхням P₁=P₀; Р₂=Р(1-y(r)/y(r₀)); Р₃=Рo(1-y(r)/y(r₀))². Розрахунки показали, що у випадку зміщення магнітної осі у середину тора та малих α кути обертального перетворення можуть обертатися в нуль на певних радіусах та викликати розщеплення магнітних поверхонь. Розподіл тиску плазми Р₁=P₀ не викликає розщеплення магнітних поверхонь. Магнітні поверхні у цьому випадку розщепляються тільки за рахунок збурень, зумовлених гвинтовою обмоткою. Авторами работы выполнены расчеты углов, обусловленных различными профилями давления плазмы в зависимости от параметра α, характеризующего профиль вакуумных углов поворота, а также от смещения магнитной оси, вызванного внешним поперечным магнитным полем. Рассмотрены три закона распределения давления плазмы по вакуумным магнитным поверхностям: Р₁=P₀; Р₂=Р(1-y(r)/y(r₀)); Р₃=P₀(1-y(r)/y(r₀))². Показано, что распределение давления плазмы Р₂=Р(1-y(r)/y(r₀)); и Р₃=P₀(1-y(r)/y(r₀))² вызывают расщепление магнитных поверхностей при rс/ro=0. Пологое распределение давления плазмы Р₁=P₀ не вызывает расщепления магнитных поверхностей. Магнитные поверхности в этом случае будут расщепляться только за счет возмущения, вызванного винтовой обмоткой.